Quantitative assessment of glenohumeral translation in professional golfers using ultrasound - Mackenzie, T. A.; Herrington, L.; Porter, S.; Funk, L. (Journal of Athletic Enhancement, 2014)
Background: Posterior hyper laxity of the glenohumeral joint could contribute to shoulder problems in golfers; hence, a measuring tool to quantify glenohumeral laxity clinically is important. Objective: Assess within-session intra-rater reliability of using Ultrasound to measure glenohumeral laxity, and quantify glenohumeral joint translation in symptom free elite golfers and non overhead athlete controls. Study design: Descriptive laboratory study Method: Ultrasound Scanning measured humeral head translation during the Drawer test in 30 asymptomatic professional golfers recruited on the PGA European Challenge Tour, and 10, asymptomatic, non overhead male athlete controls, all male and under the age of 40 years. Results: Within-session intra-rater reliability coefficients (Intraclass correlation ICC3.1) were moderate to good, with scores of more than 0.75 (95% confidence interval 0.51-0.94) for the technique and instrumentation used. Posterior translation of the humeral head was 1.29 mm greater in golfers in the non dominant/lead shoulder compared with controls. This was statistically significant when p=0.01(Mann-Whitney U test). Conclusion: Real Time Ultrasound Scanning is a reliable method of assessing posterior glenohumeral laxity in golfers. Posterior translation of the humeral head was greater in golfers in the non dominant/lead shoulder compared with controls.